WACANA KETERASINGAN PEREMPUAN DALAM NOVEL STENSILAN: STUDI KASUS KARYA ENNY ARROW - Ariska Puspita Anggraini; Dwi Susanto; Wakit Abdullah (Proceeding of International Conference on Art, Language, and Culture, 2019)
Stencil novels were so popular in the 1970s until the end of 1990s, precisely when the new order was existed. One of the most popular stencil novels was written by Enny Arrow. Her masterpiece gives abig impact for the generation. Her works present details of sexual relation and descriptionsof the human body, especially the female body, which can be able to awaken the reader's libido. The cover and illustration of the books often present pictures of sexy women. Uniquely, Enny Arrow's novels were able to get away from the tightness of the New Order regime which conditions for banning and censorship. Historically, during the New Order era women seemed to be printed in the culture of ‘controlled by husband'.That’s why the author sees the discourse of alienation in Enny Arrow's works, but how the discourse of alienation described in Enny Arrow's stencil novels? By using theory of power by Foucault, discourse of alienation is understood by the writer as a form of resistance from patriarchal domination that shapes women's understanding.